Pekan Rabu : a history of the Malay trading community of Alor Setar - Jamil, Fadzillah Jamil @ Mohd. (Universiti Sains Malaysia, 1973)
The story about the growth of the Malay trading community in this country, has been a subject hardly touched upon. Whereas, one can find reasonable number of reading aterials on such subject as Malay magic, superstitions and folk-beliefs, Malay handicrafts and folk-lore.